Determination of Site-specific NPK Fertilizer Rates for Rice Grown on Tidal Lowland - Aksani, Dila; Budianta, Dedik; Hermawan, Agus (JOURNAL OF TROPICAL SOILS, 2018)
This research aimed to determine site specific NPK fertilizer rates combined with rice straw compost application for rice grown on the tidal lowland. This research was conducted in a greenhouse in Indralaya, Ogan Ilir, South Sumatera in FebruaryÂ  until September 2017 using a factorial completely randomized design with two factors and three replications. The first factor was NPK fertilizer rate calculated based on the results of soil chemical analysis, consisting of five levels, namely 50% (D1), 75% (D2), 100% (D3), 125% (D4) and 150% (D5) of the site-specific fertilizer rate. The second factor was rice straw compost rate consisting of two levels, namely 5 Mg ha-1 (J1) and 10 Mg ha-1 (J2). The results showed that the application of 150% NPK rate and 10 Mg ha-1 rice straw compost resulted in the best effects on the rice growth grown on the tidal lowland. The application of those fertilizer doses produced the highest maximum number of tillers and productive tillers. In this regard the doses of NPK fertilizers that should be applied are 315 kg urea ha-1, 135 kg SP-36 ha-1 and 90 kg KCl ha-1.Â